Accounting of agricultural and nonagricultural impacts of irrigation and drainage Systems: A report of research in Taiwan and Sri Lanka in 2003 - International Water Management Institute (International Water Management Institute, 2004)
This paper is a collaborative research between the International Water Management Institute (IWMI) and the Agricultural Engineering Research Centre of Taiwan. This study contributes to IWMI?s program on the Comprehensive Assessment of Water Management in Agriculture. The research in 2003 consists of two components. First, research in Taiwan continues on estimating the positive and negative externalities of paddy-rice production. Second, research is being conducted in Sri Lanka to assess more broadly the impact of water resource development. In addition, two extensive literature reviews have been completed